THE TURKIC CIVILIZATION IN THE CONTEXT OF HISTORY AND GLOBALIZATION - Karybek MOLDOBAYEV (Türk Uygarlığı Araştırma ve Uygulama Merkezi Dergisi, 2023)
Genesis of the Turkic Civilization To be able to comprehend and understand the core of any type of phenomenon, it is necessary to investigate the sources of its origin, and to study when, how and why it has appeared in the historical reality. First of all, it refers to the arch-difficult system, as the phenomenon of civilization, which undoubtedly stays as the highest indicator of the public existence according to its difficulty and many-sidedness of the components and also according to the level of its development. Hence it appears that as the heavily organized public body, the phenomenon of civilization springs from different sources and the roots of this process are deep in its stratum of space and time. Proceeding from this postulate and leaning on the results of the historical investigations we try to clear up the genesis of the Turkic civilization.